“[L]ife among the dead”: Translation and Shelley’s “On a Future State” - Blake Davis, Amanda (Romanticism on the Net)

(untitled) (Université de Montréal, 2021)
Shelley’s much-neglected prose fragment, “On a Future State,” considers a future state after death in shifts between scepticism and idealistic pathos that owe more to the poet’s readings and translations of Plato’s dialogues than has been previously recognised. Following Alan Weinberg’s redating of the fragment’s composition to the winter of 1818-19, “On a Future State” looks before and after to Shelley’s translation of Plato’s Symposium in July 1818 and the Phaedo in May 1820. Centring upon “On a Future State” and Shelley’s persistent interest in “a future state,” this article explores how the fragment connects disparate modes of composition, where prose becomes an intermediary form linking translations to original poetry. “On a Future State” adumbrates Shelley’s thoughts upon translation and futurity in A Defence of Poetry (1821), embodying the poet’s claim that “the popular division into prose and verse is inadmissible in accurate philosophy.” By considering Shelley’s poetry alongside his translations of Plato, this article explores how the meditation upon death in “On a Future State” blends poetry and prose with an indebtedness to Plato’s poetic prose and his dialogue upon Socrates’ death, the Phaedo. “On a Future State” evidences how the vitalising act of translation breathes new life into the dead.